Effects of Problem-Based Learning on Biology Achievement and Instructional Satisfaction of Grade 12 Students - จะปะเกีย รุสดา; พจนตันติ ณัฐวิทย์; อินตะนัย อิสระ (Al-HIKMAH Journal, 2018)
This research aimed to study the effects of problem-based learning on biology achievement and instructional satisfaction of grade 12 students. The samples of the study were thirty-eight students of grade 12/2 in the second semester of the academic year of 2014 at Phatnawitya School, Muang District, Yala Province, Thailand. They were instructed via using problem-based learning for 12 hours. The research instruments consisted of a lesson plan for the problem-based learning under the topic of the Human and environmental sustainability, achievement test, instructional satisfaction test, the researcher’s field-note and students interview recording. The experimental research was conducted using one group pretest-posttest design. The data was analyzed by mean, standard deviation, t-test dependent group and growth score. The results were shown as follow. The biology achievement of students learning by problem- based learning approach was higher than the pre-test mean score of at the significant level of .01. Growth score among the students 68.42% of them were in high level and 31.58% of them were in medium level. Biology achievement level are good. Instructional satisfaction was high and students were recognize, analyze and solve problems on their own under working together. Assertive comment, enthusiasm, responsibility, able to find information themselves and a summary of what was learned. As a result, students to learn deeply and happily.